Negotiating Pedagogic Researcher Identity by Two College English Teachers in China: A Social Network Perspective - Wei Zeng; Letitia Fickel (International Journal of Contemporary Educational Research)
Scholarship of Teaching and Learning (SoTL) or pedagogic research (PedR) has become an international movement that encourages academics to use research-informed approaches to understand and enhance their teaching. However, the definition and understanding of SoTL/ PedR have been ambiguous, impacting career progression, orientation of scholarship activities and academics’ perception of undertaking such activities. This article adopts social network perspective to understand the SoTL/PedR experiences of two academics with a focus on teaching ---College English (CE) teachers working at a Chinese tertiary institution as they navigate their identities in a higher education (HE) context that attempts to promote SoTL/PedR. An integrated framework for understanding identity in individual social network of practice (INoP) is used to examine the complex nature of identity negotiation. Multiple networks and communities are identified. The juxtaposition of ties and communities reflects the complexity of PedR discourse, in which the stratification of knowledge and power relations sustain the boundaries of networks or communities. Two participants experienced complexity of subjectivities and negotiated a range of positions, e.g., CE teacher versus ‘more professional’ English Major (EM) teacher, pedagogic researcher versus ‘real’ researcher, educational researcher versus ‘superb’ disciplinary researcher. The article also discerns a collective subordination of CE teachers’ joint endeavors of researching their teaching practice to dominant research discourse. The study contributes to our insights into cultivating practice-oriented, problem solving-focused, research-informed PedR communities and networks characterized by recognition, trust, and respect.